2015
DOI: 10.1136/jramc-2014-000372
|View full text |Cite
|
Sign up to set email alerts
|

Sudden onset hemiplegia at high altitude

Abstract: Travel to high altitude and the incumbent exposure to hypobaric hypoxia leads to a prothrombotic state. This may increase the likelihood of thromboembolic events, including stroke, in otherwise healthy individuals. While there have been sporadic anecdotal reports of 'stroke-like' syndromes at high altitude for over 100 years, there are surprisingly few detailed reports supported by imaging.This report describes a case of posterior circulation infarct thought to be due to a paradoxical embolus through a patent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The presence of PFO could make this population even susceptible to these environmental challenges. In fact, studies have shown that people with PFO in high altitude environment fail to increase their pulmonary gas exchange efficiency, potentially due to the right to left intracardiac shunt [ 24 ], and the hypoxia condition leads to prothrombotic state and pulmonary hypertension [ 25 ], which could lead to more paradoxical embolism formation [ 26 ]. All these risk factors set a non-suitable condition for people with PFO, making them easier to develop brain ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PFO could make this population even susceptible to these environmental challenges. In fact, studies have shown that people with PFO in high altitude environment fail to increase their pulmonary gas exchange efficiency, potentially due to the right to left intracardiac shunt [ 24 ], and the hypoxia condition leads to prothrombotic state and pulmonary hypertension [ 25 ], which could lead to more paradoxical embolism formation [ 26 ]. All these risk factors set a non-suitable condition for people with PFO, making them easier to develop brain ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…These search terms revealed 236 citations. After identifying relevant articles that discussed stroke at high altitude, and cross referencing, we found one review (Ortiz-Prado and Dunn, 2011), eight case series (including pooled analysis) (Razdan et al, 1989;Jaillard et al, 1995;al Tahan et al, 1998;Jha et al, 2002;Niaz and Nayyar, 2003;Mahajan et al, 2004;Dhiman et al, 2018;Zhang et al, 2020), and seven case reports (Murdoch, 1995;Dietz and McKiel, 2000;Bandyopadhyay et al, 2002;Wilson et al, 2011;Chan et al, 2012;Yanamandra et al, 2014;Chandler and Mellor, 2016) that were considered appropriate for this review. Of the eight case series, four were from high altitude, including a pooled analysis (more than 2,500 m) ( Jaillard et al, 1995;Jha et al, 2002;Niaz and Nayyar, 2003;Zhang et al, 2020), and four were from moderate altitude (1,500-2,500 m) (Razdan et al, 1989;al Tahan et al, 1998;Mahajan et al, 2004;Dhiman et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…This increase was found particularly in younger age, mostly between 20 and 45 years. The stroke rates were found to be 10 times (Niaz and Nayyar, 2003) to 13 times (Razdan et al, 1989;Jaillard et al, 1995;al Tahan et al, 1998;Dietz and McKiel, 2000;Anand et al, 2001;Bandyopadhyay et al, 2002;Jha et al, 2002;Mahajan et al, 2004;Wilson et al, 2011;Chan et al, 2012;Yanamandra et al, 2014;Murdoch, 2015;Chandler and Mellor, 2016;Dhiman et al, 2018;Zhang et al, 2020) higher among people living at very high altitude and extremely high altitude.…”
Section: Epidemiology Of Stroke At High Altitudementioning
confidence: 98%
See 1 more Smart Citation